Aegla platensis (Schimit, 1942): um complexo de espécies? Evidências a partir do gene mitocondrial COI - Hauschild, Caroline Bacelar (2011)
Aeglid crabs have attracted researchers because they represent the only anomuran family entirely restricted to continental waters, besides being endemic to the tropical and temperate regions of South America, occurring in streams, creeks, rivers, lagoons and caves. These crabs are becoming more and more restricted to the headwaters due to their necessity of clean and well oxygenated water. The family Aeglidae encompasses about 70 species described up to now, and of these, 23 are found in Rio Grande do Sul state (RS). Aegla platensis is one of the few species found in the three hydrographic basins of RS. Due to its broad distribution, this study investigates the taxonomic status of A. platensis occurring in Uruguay and Guaíba basins. Analysis were carried out with partial sequences of the mitochondrial genes 16S, COI and COII individually as well as the three genes concatenated. Phylogenetic analysis were performed using Neighbor-Joining, Maximum Parsimony, Maximum Likelihood, and Bayesian Inference, which presented high statistical supports, suggesting the hypothesis that A. platensis may constitute a complex with at least three species. These results are in agreement with the other analyses realized in the present study.